2012
DOI: 10.1016/j.bbr.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Use it or lose it: How neurogenesis keeps the brain fit for learning

Abstract: The presence of new neurons in the adult hippocampus indicates that this structure incorporates new neurons into its circuitry and uses them for some function related to learning and/or related thought processes. Their generation depends on a variety of factors ranging from age to aerobic exercise to sexual behavior to alcohol consumption. However, most of the cells will die unless the animal engages in some kind of effortful learning experience when the cells are about one week of age. If learning does occur,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 107 publications
(163 reference statements)
2
135
0
Order By: Relevance
“…In particular, hippocampal-dependent learning promotes the survival of newborn cells generated 1 week before training, as a function of task difficulty. Trace eye blink conditioning and spatial learning (reference memory or delayed matching to place) exert a survival-promoting effect (Shors et al, 2012), whereas active shock avoidance and fear contextual memory are insufficient to change cell survival (Pham et al, 2005;Van der Borght et al, 2005;LopezFernandez et al, 2007). More recently, we have discovered that learning-induced survival of these immature neurons depends upon the elimination of youngest newborn cells at a specific developmental period (Drapeau et al, 2007;Dupret et al, 2007;Tronel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hippocampal-dependent learning promotes the survival of newborn cells generated 1 week before training, as a function of task difficulty. Trace eye blink conditioning and spatial learning (reference memory or delayed matching to place) exert a survival-promoting effect (Shors et al, 2012), whereas active shock avoidance and fear contextual memory are insufficient to change cell survival (Pham et al, 2005;Van der Borght et al, 2005;LopezFernandez et al, 2007). More recently, we have discovered that learning-induced survival of these immature neurons depends upon the elimination of youngest newborn cells at a specific developmental period (Drapeau et al, 2007;Dupret et al, 2007;Tronel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…"Use It or Lose It" in Free-Living Mammals Shors et al (2012) have formulated the "use-itor-lose-it" concept for AHN in laboratory rodents, as many behavioral experiments that include some forms of learning increase the survival rates of young cells. Free-living mammals have to cope with a multitude and, in many ways, continually changing stimuli throughout their life.…”
Section: Functional Aspects Of Hippocampal Neurogenesis Variation In mentioning
confidence: 99%
“…For example, the survival of new brain cells is enhanced by spatial navigation learning during Morris water maze tests in rats and mice [reviewed in Shors, 2008;Shors et al, 2012]. Similarly, Hoshooley and Sherry [2007] showed that greater neuron recruitment in the hippocampus is associated with food caching in adult black-capped chickadees, i.e.…”
Section: Introductionmentioning
confidence: 99%